Alles zum Wohle des Kindes? Aktuelle Probleme des Kindschaftsrechts 2. Familienrechtliches Forum Göttingen - Coester-Waltjen, Dagmar; Lipp, Volker; Schumann, Eva; Veit, Barbara (Universitätsverlag Göttingen, 2012)
This volume contains the lectures of the 2nd Family Law Forum in Göttingen, July 2nd, 2011. Major topic is Child Safety Law and the threats of child's well-being.